2018
DOI: 10.3390/app8020193
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Navigation System for Unmanned Surface Vehicles in Realistic Sea Environments

Abstract: Abstract:In recent years, unmanned surface vehicles (USVs) have received notable attention because of their many advantages in civilian and military applications. To improve the autonomy of USVs, this paper describes a complete automatic navigation system (ANS) with a path planning subsystem (PPS) and collision avoidance subsystem (CAS). The PPS based on the dynamic domain tunable fast marching square (DTFMS) method is able to build an environment model from a real electronic chart, where both static and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Furthermore, most of the USV research found in the last decade falls into two configurations: double-hulled ( [11]), and mono-hull ( [12,13]). The configuration most used in research is the double-hulled configuration, e.g., catamaran.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the USV research found in the last decade falls into two configurations: double-hulled ( [11]), and mono-hull ( [12,13]). The configuration most used in research is the double-hulled configuration, e.g., catamaran.…”
Section: State Of the Artmentioning
confidence: 99%
“…The previous works found employing double-hull platforms focus in developing robust modeling and control approaches to improve the vehicles autonomous navigation [11,15,16]. In these works, the USV employed are off-the-shelf vehicles that have not being built from the scratch.…”
Section: State Of the Artmentioning
confidence: 99%
“…USVs are remotely controlled or can operate in autonomous mode, using various sensors, communication and control systems, as well as navigation technologies [ 3 , 4 ]. Unmanned vessels have many advantages such as the ability to carry out long-term missions, work in hard-to-reach places, reduce risk for the crew and the ability to collect large amounts of data [ 5 , 6 , 7 ] using various sensors such as cameras, echosounders, RAdio Detection AND Ranging (RADAR), Light Detection And Ranging (LiDAR), Inertial Navigation System (INS), Global Navigation Satellite System (GNSS), sonars, etc. [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal route planning in marine applications is nowadays well developed [26] (primarily, in the context of unmanned surface vehicles). Various approaches include deep reinforcement learning [27], artificial potential field [28], trajectory branching [29], Voronoi diagrams [30], iterative genetic algorithms [31], and grid-based methods such as fast marching [32], [33], Dijkstra [34], A * and its modifications [35]- [37]. In this article, we propose a modification of the Dijkstra algorithm.…”
Section: Introductionmentioning
confidence: 99%